Influence of Bio-based Nutrient Sources on Organic Cherry Tomato Cv. Golden Purna Cultivation (South Asian Journal of Agriculture, 2026)
The experiment was conducted from October 2025 to February 2026 at the Horticulture Farm of Sher-e-Bangla Agricultural University, Dhaka, Bangladesh, to investigate the effects of different organic substrates on the growth, yield, and quality of Golden Purna cherry tomato. The experiment consisted of six treatment combinations, namely: T₁ = Cow dung alone; T₂ = Vermicompost alone; T₃ = Cow dung + Mustard oilcake; T₄ = Vermicompost + Mustard oilcake; T₅ = Cow dung + Mustard oilcake + Bone meal; and T₆ = Vermicompost + Mustard oilcake + Bone meal. The experiment was laid out in a Randomized Complete Block Design (RCBD) with three replications. Significant variations were observed among the treatments for growth, yield, and quality parameters of cherry tomato. Among the treatments, T₆ (Vermicompost + Mustard oilcake + Bone meal) exhibited the superior performance in terms of growth and yield attributes, recording the maximum plant height (209.0 cm), number of branches (7.0 plant⁻¹), number of fruits (1050.4 plant⁻¹), number of fruits per cluster (131.3), fruit yield (11.7 kg plant⁻¹), and yield (36.4 t ha⁻¹). In contrast, the lowest fruit yield (3.2 kg plant⁻¹ and 9.4 t ha⁻¹) was observed in T₁ (Cow dung alone). Considering the overall performance, T₆ (VC + MoC + BM) was found to be the most effective treatment for improving the growth, yield, and quality attributes of SAU Yellow Cherry Tomato.South Asian J. Agric. Vol. 12, No. 1, Jun., 2026: 44-54